1966
DOI: 10.1126/science.153.3733.305
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Significance of Polyploidy in the Pteridophyta

Abstract: Polyploidy occurs in the heterosporous and homosporous Pteridophyta, but with a much higher frequency in the latter. Ninety-six percent of the homosporous Pteridophyta show a gametic chromosome number greater than 27, whereas 90 percent of the heterosporous ones possess a gametic chromosome number less than 28. Ultrafrequent establishment of poly- ploidy in the homosporous Pteridophy- ta appears to be necessary to create and maintain genetic variation in the face of the homozygotizing effects of habitual self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
94
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(101 citation statements)
references
References 4 publications
7
94
0
Order By: Relevance
“…Ferns have especially high chromosome numbers, with Ophioglossum reticulatum possessing the highest known chromosome count among extant eukaryotes (n > 600; Khandelwal, 1990). However, a distinction should be made between heterosporous ferns that have chromosome counts similar to angiosperms (n = 15.99 on average) and homosporous ferns where the chromosome count is more than 3 times higher (n = 57.05 on average; Klekowski and Baker, 1966). This early work investigated a limited number of homosporous ferns and concluded that selfing was a common mechanism of reproduction (Klekowski and Baker, 1966).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferns have especially high chromosome numbers, with Ophioglossum reticulatum possessing the highest known chromosome count among extant eukaryotes (n > 600; Khandelwal, 1990). However, a distinction should be made between heterosporous ferns that have chromosome counts similar to angiosperms (n = 15.99 on average) and homosporous ferns where the chromosome count is more than 3 times higher (n = 57.05 on average; Klekowski and Baker, 1966). This early work investigated a limited number of homosporous ferns and concluded that selfing was a common mechanism of reproduction (Klekowski and Baker, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…However, a distinction should be made between heterosporous ferns that have chromosome counts similar to angiosperms (n = 15.99 on average) and homosporous ferns where the chromosome count is more than 3 times higher (n = 57.05 on average; Klekowski and Baker, 1966). This early work investigated a limited number of homosporous ferns and concluded that selfing was a common mechanism of reproduction (Klekowski and Baker, 1966). Combined with later observations of unusually high numbers of chromosomes in homosporous ferns (and the resultant assumption that this was due to polyploidy), the hypothesis emerged that polyploidy would present a plausible mechanism allowing the generation of novel genetic material to avoid homozygous inbreeding depression by pairing of homoeologous rather than homologous chromosomes during meiosis (Klekowski, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The average chromosome number in homosporous ferns was estimated to be n ¼ 57.05, as opposed to n ¼ 15.99 in angiosperms (Klekowski and Baker 1966). Angiosperm species with chromosome numbers .n ¼ 14 are generally considered to be polyploid (Grant 1981).…”
mentioning
confidence: 99%
“…The average haploid chromosome number for homosporous ferns, 57.05 (1), is so high that up to 95% of all fern species have been considered polyploid (2). However, since the essence of polyploidy is the number of component genomes and not the number ofchromosomes, the genetic significance of such high polyploidy estimates may be questioned.…”
mentioning
confidence: 99%